Teaching Cases and Reflections on "Saving Mother Earth" - Zhao, Chaojin (Journal of Theory and Practice of Social Science, 2024)
Taking the practical lesson of moral education "Saving the Earth Mother" as an example, the article discusses how to use network resources to improve the teaching effect of moral education classroom. The author believes that the moral education classroom can be improved through these three ways:use network resources, create situations, and stimulate learning interest;Use network resources, effectively guide and break through the key and difficult points of teaching; Guide students to use network resources to cultivate their information literacy. Practice has proved that reasonable use of network resources for teaching has achieved the ideal effect that traditional teaching cannot match.